Wild edible plants used by communities in and around selected forest reserves of Teso-Karamoja region, Uganda - Samuel Ojelel; Patrick Mucunguzi; Esther Katuura; Esezah K. Kakudidi; Mary Namaganda; James Kalema (BMC, 2019)
Abstract Background The consumption of wild plants is an ancient tradition which serves multiple purposes. Cognizant that Teso-Karamoja region is frequently affected by food scarcity and is not adequately surveyed for its flora, this study sought to establish an inventory and use of wild edible plants by the communities living in and around the forest reserves. Methods Data was collected using semi-structured questionnaires administered to 240 respondents living in and around eight forest reserves between November 2017 and May 2018. One focus group discussion (8-12 members) per forest reserve and field excursions to collect the plant voucher specimens were also conducted. The data was analyzed using descriptive statistics, relative frequency of citation (RFC), and the factor of informants' consensus (FIC). Results A total of 100 plant species in 47 families were reported as edible. Carissa spinarum, Strychnos innocua, Balanites aegyptiaca, Tamarindus indica, and Ximenia americana presented the highest RFC, while the families Rubiaceae, Fabaceae, Anacardiaceae, Amaranthaceae, and Moraceae had more than five species each. Grasses (Poaceae) comprised only 1% of the edible species and trees 35%, while shrubs were the most important source of wild food (RFC = 0.47). The fruits contributed 63% while leaves (29%), seeds (9%), tubers (5%), and gum (1%). The fruits were considered as the most important use category (RFC = 0.78). Respondent homogeneity was none for gum but very high for seeds (FIC - 0.93). Only 36% of species are cooked, while 64% are eaten in raw. Harvesting is done rudimentarily by digging (5%), collecting from the ground (fruits that fall down) (13%), and plucking from mother plants (82%). Only 9% of the species were collected throughout the year, 27% in the dry season, and 64% in the rainy season. The consumption of these plants is attributed to food scarcity, spicing staple food, nutri-medicinal value, cultural practice, and delicacy. Conclusion A high diversity of wild edible plant species exists in the forest reserves of Teso-Karamoja region. The shrubs and fruits are the most locally important life forms and use category, respectively. These edible plant species are important throughout the year because their consumption serves multiple purposes.